De novo-engineered transcription activator-like effector (TALE) hybrid nuclease with novel DNA binding specificity creates double-strand breaks - Mahfouz, Magdy M. (National Academy of Sciences, 2011)
Site-specific and rare cutting nucleases are valuable tools for genome engineering. The generation of double-strand DNA breaks (DSBs) promotes homologous recombination in eukaryotes and can facilitate gene targeting, additions, deletions, and inactivation. Zinc finger nucleases have been used to generate DSBs and subsequently, for genome editing but with low efficiency and reproducibility. The transcription activator-like family of type III effectors (TALEs) contains a central domain of tandem repeats that could be engineered to bind specific DNA targets. Here, we report the generation of a Hax3-based hybrid TALE nuclease with a user-selected DNA binding specificity. We show that the engineered TALE nuclease can bind to its target sequence in vitro and that the homodimeric TALE nuclease can cleave double-stranded DNA in vitro if the DNA binding sites have the proper spacing and orientation. Transient expression assays in tobacco leaves suggest that the hybrid nuclease creates DSB in its target sequence, which is subsequently repaired by nonhomologous end-joining repair. Taken together, our data show the feasibility of engineering TALE-based hybrid nucleases capable of generating site-specific DSBs and the great potential for site-specific genome modification in plants and eukaryotes in general.